Sistem Pengolahan Data Prestasi Mahasiswa di Program Studi Sistem Informasi Kampus XYZ - Samosir, Ridha Sefina (I-STATEMENT, 2016)
This study aims to develop a computer-based information system to processing student achievement data both in academic and non-academic courses. Results of the study provide benefits in assisting the study program to simplify and accelerate the management of student achievement data. Research method taken was qualitative through several means, namely literature review, observation and interviews. The literature review was conducted to study the concept and theoretical research support, while observation and interviews conducted directly into existing courses to obtain supporting data such as student achievement data and data students. Student achievement data processing system developed by the waterfall approach. The tools that used was VB.Net programming language and MySQL database.